Quantum charge pumping in graphene-based devices: when lattice defects do help - Ingaramo, Lucas Hernán (2013)
Quantum charge pumping, the quantum coherent generation of a dc current at zero bias through time-dependent potentials, provides outstanding opportunities for metrology and the development of nanodevices. The long electronic coherence times and high quality of the crystal structure of graphene may provide suitable building blocks for such quantum pumps. Here, we focus in adiabatic quantum pumping through graphene nanoribbons in the Fabry-Perot regime highlighting the crucial role of defects by using atomistic simulations. We show that even a single defect added to the pristine structure may produce a two orders of magnitude increase in the pumped charge.